2001
DOI: 10.1002/cne.1090
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of preproadrenomedullin mRNA in the rat central nervous system and its modulation by physiological stressors

Abstract: Adrenomedullin (ADM), encoded by the preproadrenomedullin (ppADM) gene, exerts multiple effects in a wide variety of peripheral and central tissues. Although ADM-like immunoreactivity has been shown to be widely distributed throughout the rat central nervous system (CNS), the detailed distribution of ppADM gene expression in the CNS and its modulation by physiological stimuli remain unknown. In our study, in situ hybridization was used to localize ppADM mRNA in the rat brain and to quantify its levels after ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 66 publications
(62 reference statements)
2
34
1
Order By: Relevance
“…ADM and its receptor have been shown to be expressed in the central nervous system (CNS) and its cellular components [10,28,29]. The direct effects of ADM on sympathetic nerve activity in conscious rats have been observed and these studies are consistant with the observations reported by Takekoshi and colleagues [30], who showed that in anesthetized rats, icv ADM induces an increase in preganglionic sympathetic discharge.…”
mentioning
confidence: 75%
“…ADM and its receptor have been shown to be expressed in the central nervous system (CNS) and its cellular components [10,28,29]. The direct effects of ADM on sympathetic nerve activity in conscious rats have been observed and these studies are consistant with the observations reported by Takekoshi and colleagues [30], who showed that in anesthetized rats, icv ADM induces an increase in preganglionic sympathetic discharge.…”
mentioning
confidence: 75%
“…In a similar way, s.c. injection of PAMP provoked an elevation on ACTH and corticosterone in the rat (31). In addition, several articles demonstrate that when humans or experimental animals are subjected to a diverse battery of stressors (restraint, dehydration, cold, disease, acute exercise, or psychological pressure) the common response is a sharp elevation on the levels of tissue and circulating AM (32)(33)(34). In our mice lacking adm in the brain, we observed a behavior consistent with higher basal stress levels when compared to their wild-type littermates.…”
Section: Discussionmentioning
confidence: 99%
“…AM is a 52 aa peptide and is broadly distributed in the CNS (Serrano et al, 2000;Shan and Krukoff, 2001). This peptide belongs to a family that includes AM2 (intermedin) (Roh et al, 2004), CGRP, amylin (Poyner et al, 2002), and calcitonin receptor-activating peptides (Katafuchi et al, 2003a,b).…”
Section: Introductionmentioning
confidence: 99%